Producing Time Series Data for Income Distribution: Sources, Methods and Techniques - Tony Atkinson; Andrea Brandolini; Timothy Smeeding (Luxembourg Income Study (LIS), 2001)
This chapter addresses the important issue of the quality of time series data on income distribution. We hope to suggest both standards and practice patterns that will improve the production and use of time series data on inequality. Thus, we address three groups: primary data producers; secondary data producers (who assemble databanks from primary data sources), and users. We consider measurement error in both theory and practice. Along the way we include a number of practical suggestions for improving the comparability of time series data and trend analyses for income distribution.
Keywords: 330; Einkommensverteilung; Statistische Methode; Zeitreihenanalyse; Welt